Charlie Bone and the beast [compact disc, unabridged] - Nimmo, Jenny (Nimmo, Jenny. Children of the red king (Audio), 2008)
When Asa Pike, a Bloor's Academy student with the ability to change into a beast at dusk, disappears and a new student enrolls, Charlie Bone and his friends struggle to rescue Asa and uncover the new student's true identity.